2012
DOI: 10.1124/jpet.112.193789
|View full text |Cite
|
Sign up to set email alerts
|

UniqueO-Methoxyethyl Ribose-DNA Chimeric Oligonucleotide Induces an Atypical Melanoma Differentiation-Associated Gene 5-Dependent Induction of Type I Interferon Response

Abstract: Antisense oligonucleotides (ASO) containing 2Ј-O-methoxyethyl ribose (2Ј-MOE) modifications have been shown to possess both excellent pharmacokinetic properties and robust pharmacological activity in several animal models of human disease. 2Ј-MOE ASOs are generally well tolerated, displaying minimal to mild proinflammatory effect at doses far exceeding therapeutic doses. Although the vast majority of 2Ј-MOE ASOs are safe and well tolerated, a small subset of ASOs inducing acute inflammation in mice has been id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Similar to ISIS 116847, no change in inflammatory signaling was observed in knockout animals deficient in MyD88 and TRIF. Interestingly, this study demonstrated that two cytosolic receptors, melanoma-differentiation associated-5 (MDA-5) and IFN-b promoter stimulator-1 (IPS-1) were involved in the inflammatory reaction to ISIS 147420, but retinoic acid inducible gene-1 (RIG-1) was not [64]. Both IPS-1 and RIG-1 are pattern recognition receptors that are capable of recognizing foreign nucleic acids.…”
Section: Second-and Third-generation Phosphorothioate Asosmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar to ISIS 116847, no change in inflammatory signaling was observed in knockout animals deficient in MyD88 and TRIF. Interestingly, this study demonstrated that two cytosolic receptors, melanoma-differentiation associated-5 (MDA-5) and IFN-b promoter stimulator-1 (IPS-1) were involved in the inflammatory reaction to ISIS 147420, but retinoic acid inducible gene-1 (RIG-1) was not [64]. Both IPS-1 and RIG-1 are pattern recognition receptors that are capable of recognizing foreign nucleic acids.…”
Section: Second-and Third-generation Phosphorothioate Asosmentioning
confidence: 93%
“…For NATs, the majority of available studies have focused on TLRs (TLR3, TLR7/8 and TLR9) to explain observed immunostimulation [63,64,[165][166][167][168]. However in many cases, inhibiting or eliminating TLRs from test systems reduced immunostimulation but did not eliminate it, leaving a gap in the understanding of the mechanism(s) [63,64].…”
Section: Expert Opinionmentioning
confidence: 95%
See 1 more Smart Citation
“…The shorter basepair length of most LNA gapmers (based on their higher binding efficiency) seems to reduce their proinflammatory potential as compared to other backbones. The basis for the sequence specificity in rodents are sequence motifs that are recognized by pathogen-associated molecular pattern (PAMP) receptors, such as the nucleic acidsensing TLR receptors (Agrawal and Kandimalla 2004;Senn, Burel, and Henry 2005;Richardt-Pargmann and Vollmer 2009;Burel et al 2012;Burel et al 2013). These attributes have been exploited for immunomodulatory drug indications by industry (Krieg 1998(Krieg , 1999Henry et al 1999).…”
Section: Hybridization-independent Proinflammatory Effects (Challengementioning
confidence: 99%
“…The microarray gene expression analysis showed several downregulated genes predicted to be because of off-target hybridization of HDO (Table 2). In addition, sequence-dependent and hybridization-independent immunestimulatory adverse effects mediated by activation of toll-like innate receptors 52,53 can also be a concern. Finally, a sequenceand hybridization-independent chemical property of nucleotide analogues and chemical modifications can cause liver dysfunction 51,[54][55][56][57] .…”
Section: Resultsmentioning
confidence: 99%